Cetuximab functionalized chitosan/hyaluronic acid-based nanoparticles loaded with cabazitaxel enhances anti-tumor efficacy in DMBA-induced breast cancer model in rats through spatial targeting - Jha, Abhishek; Goswami, Pooja; Kumar, Manish; Bharti, Kanchan; Manjit, Manjit; Satpute, Amol P.; Gupta, Ashutosh; Moorkoth, Sudheer; Koch, Biplob; Mishra, Brahmeshwar (Chemical physics impact, 2024)
The article discusses the ionic gelation of cationic chitosan (CS) with anionic hyaluronic acid (HA) sodium salt to form nanoparticles in the range of 125 nm. The particles were further functionalized with cetuximab to endow it with the ability to spatially target the tumor over-expressing EGFR. Solid-state characterization of the particles using XRD, FTIR, and DSC revealed the formation of stable nanoparticles with Cabazitaxel loaded in the amorphous nanostructure. XPS study used to assess the surface characteristics indicated that the cetuximab was successfully anchored on the surface of the particle. The prepared CS-HA-Cmab-NP elicited a pH-responsive drug release behavior due to the presence of CS in the matrix. In vitro performance of the nanoparticles was evaluated on MDA-MB-231 breast cancer cell lines showed overall increase in efficacy. In vivo pharmacokinetic and anti-tumor effect evaluated in female Sprague Dawley rats indicated that the Cmab-conjugated nanoparticles improved half-life of cabazitaxel and tumor reduction capability with higher survival rate and lower reduction in body weight. The results indicate that CS/HA nanoparticles anchored with cetuximab show enhanced efficacy in reducing the breast cancer tumor in DMBA-induced breast tumor model through spatial targeting, consequently reducing the systemic toxicity. [Display omitted]